Indicadores de Ciência, Tecnologia & Inovação: análise da produção científica e tecnológica da área de conhecimento em Engenharia Civil na Base de dados da Web of Science - Soares, Patrícia Bourguignon (2014)
This dissertation deals with the analysis of international and Brazilian scientific and technological production in the Civil Engineering knowledge field, through Bibliometric indicators. The Civil Engineering field was chosen because of its relevance to the country's economic development. However, in absolute and relative terms, it is among the latest technologically sectors of the economy. The Bibliometrics is a discipline with multidisciplinary range that studies the use and quantitative aspects of scientific production registered. The scientific production indicators are subject of analysis of several knowledge fields, both for the planning and execution of public policies of various sectors and the greater knowledge of the scientific community about the system in which it is inserted. The methodology used for the design of this explanatory descriptive study was the documentary and bibliometric analysis based on data from scientific publications, over the period 1970 to 2012, and data from technological publications, over the period 2001 to 2012, all of the Civil Engineering field indexed in the following databases: Science Citattion Index Expanded (SCI); Social Science Citation Index (SSCI); Conference Proceedings Citation Index (CPCI) and Derwent Innovations Index (DII), which make up the multidisciplinary database of Web of Science (WoS). The information were quantified and qualified with aid of bibliometric VantagePoint® software. The results obtained confirmed the low number of scientific and technological publications in the field of Civil Engineering of authors affiliated to teaching and research institutions in Brazil when compared to those of industrialized countries. There are a number of strong conditions that exceed the power and influence of the Academy, making it difficult and limiting the spread of Brazilian research and patents related to factors of systemic and cultural character. The possibility of analyzing scientific and technological production indicators on Civil Engineering contributes to create policies that, if used by funding agencies, can subsidize more substantiated investments by Governments and the private sector, as is done for other industrial sectors.